Psychological adjustment of women after oncological surgery and at the end of treatment - Szczepańska-Gieracha, Joanna; Malicka, Iwona; Rymaszewska, Joanna; Woźniewski, Marek (Contemporary Oncology/Współczesna Onkologia, 2010)
Aim of study: To analyse psychological adjustment among women with tumours in the initial period of oncological treatment and after its completion. Material and methods : 77 women (average age 58.4) treated due to cancer were divided into two groups: 1) patients of the Lower Silesian Oncology Centre (n = 40) who were examined on the fifth day after surgery of breast cancer or reproductive organ tumour, 2) women who participated in a rehabilitation programme after hospital and outpatient treatment without symptoms of recurrence of disease (average time after treatment 6.8 years), n = 37. Mini-MAC, Satisfaction with Life Scale and interview of leisure time, physical activity before and after treatment were used in all women. Results: Intensity of positive adjustment attained very high values (48.2; SD ± 5.0) during hospital treatment of cancer. It expressed mobilization of strong defensive mechanisms, whose purpose was to reduce negative adjustment. After successful oncological treatment (min. 6 years without recurrence of disease) intensity of positive adjustment decreased significantly (43.8; SD ± 4.5; p = 0.002) without a considerable drop of negative adjustment. However, values of these processes strongly varied, which indicates individual diversity of negative emotions. Conclusions: Therapeutic procedures for women after breast cancer treatment should be differentiated according to intensity and variety of negative adjustment. Type of therapeutic procedures should also depend on stage of cancer treatment.